From waste to innovation: Bioentrepreneurship skills through project-based learning in biology education - Nuzula Khoiro Ummah; Nur Ducha; Dyah Hariani; Endang Susantini; Fida Rachmadiarti; Muhammad Fajar Faliasthiunus Pradipta (University of Muhammadiyah Malang, 2026)
Background: Project-Based Learning (PjBL) offers a relevant approach for linking biology education with sustainability and entrepreneurship. However, existing studies have generally examined PjBL, entrepreneurship education, and biological waste utilization separately, leaving limited understanding of how their integration can foster bioentrepreneurship. Objectives: This review aimed to analyze the role of PjBL in developing bioentrepreneurship skills, particularly through biological waste utilization. Methods: A Systematic Literature Review (SLR) was conducted on ten Scopus-indexed articles, complemented by bibliometric analysis using VOSviewer. Results: Topics such as